Analisis Manajemen Resiko Calon Jamaah Umroh (Studi di Desa Talang Tinggi Kabupaten Seluma) - Indra Heriyantoni Pratama; Supardi Mursalin; Khozin Zaki (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the risk management faced by prospective Umrah pilgrims, particularly victims of Umrah Package fraud in Talang Tinggi Village, Seluma Regency, this study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research informants consisted of prospective Umrah pilgrims, fraud victims, and umrah travel agencies. The result show that prospective Umrah pilgrims face various risk, including administrative, operational,legal, economic, social, and psychological risks. The most dominant risks are economic and legal risks, which cause financial losses and uncertainty about departure. The implementation of risk management is carried out through the stages of identification, analysis, evaluation, and risk mitigation. Recommended strategies include increasing pilgrim literacy regarding travel legality, transparency ind fund management, strengthening internal coordination of travel agencies, and emotional support for victims. The impelentation of appropriate risk management is expected to minimize the potential for fraud and increase protection for prospective Umrah pilgrims